2016
DOI: 10.1890/15-1710.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intraspecific diversity on survivorship, growth, and recruitment of the eastern oyster across sites

Abstract: Intraspecific diversity, particularly of foundation species, can significantly affect population, community, and ecosystem processes. Examining how genetic diversity relates to demographic traits provides a key mechanistic link from genotypic and phenotypic variation of taxa with complex life histories to their population dynamics. We conducted a field experiment to assess how two metrics of intraspecific diversity (cohort diversity, the number of independent juvenile cohorts created from different adult sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 71 publications
2
31
1
Order By: Relevance
“…Similarly, in a prior study using the same oyster cohorts analyzed here, we found higher recruitment of juvenile oysters to experimental assemblages created from four juvenile oyster cohorts (i.e., lines produced in a hatchery from wild stocks) compared to those from only one or two cohorts (Hanley et al. ). Survivorship of juvenile oysters was also associated with decreasing genetic relatedness (Hanley et al.…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…Similarly, in a prior study using the same oyster cohorts analyzed here, we found higher recruitment of juvenile oysters to experimental assemblages created from four juvenile oyster cohorts (i.e., lines produced in a hatchery from wild stocks) compared to those from only one or two cohorts (Hanley et al. ). Survivorship of juvenile oysters was also associated with decreasing genetic relatedness (Hanley et al.…”
Section: Methodssupporting
confidence: 81%
“…These cohorts were used in prior studies to examine the effects of cohort diversity (the number of cohorts) on oyster performance (Hanley et al. ) and the potential for local adaptation across cohorts (Hughes et al. ; Appendix ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, different metrics of genetic variation appear to have different effects on the outcome of ecological interactions (Abbott et al. 2017; Hanley, Hughes, Williams, Garland & Kimbro, 2016; Jousset et al., 2011), clouding the mechanistic interpretation of the effects of genetic variation in ecology.…”
Section: Introductionmentioning
confidence: 99%
“…, Hanley et al. ). For instance, if kin selection operates, then siblings are predicted to have lower competition and higher performance than non‐siblings; alternatively, niche partitioning predicts reduced competition and increased overall performance for non‐siblings compared to siblings (File et al.…”
Section: Introductionmentioning
confidence: 99%
“…, Hanley et al. ). Life history stage is also often confounded with mode of reproduction: manipulations of plants focus on clonal reproduction, whereas manipulations of invertebrates typically examine sexual reproduction (Aguirre and Marshall ).…”
Section: Introductionmentioning
confidence: 99%